When Passionate Leadership Stimulates Enduring Change : A Transformational Capacity Development Anecdote from Uganda - Matta, Nadim (World Bank, Washington, DC, 2012)
This paper from the water sector in Uganda turns on its head conventional wisdom about capacity growth and how long it takes to effect enduring change. This example of a transformational process that was driven by passionate leadership and, contrary to popular development wisdom, was front-ended by short-term results producing initiatives that led to longer-term impact. The experience of the National Water and Sewerage Corporation (NWSC) in Uganda reflects a tripartite relationship among results achievement, capacity development, and performance improvement. Within a couple of years, NWSC went from being a fiscally and operationally dysfunctional utility to a financially sustainable and efficient service provider. The story of this transformation and conclusions on how charismatic leaders can cause profound changes within a short time frame are outlined in this paper.